The Impact of Capital on Bank Profitability in the United Kingdom and Australia - JIAYING, YUAN (2020)
The primary purpose of our paper is to investigate the association between capital and bank profitability. The sample includes 365 banks in the United Kingdom and Australia from the period of 2011 to 2019. We employ two-step System Generalized Methods of Moments to do empirical analysis to resolve the issues of endogeneity, heteroscedasticity, and the persistence of profitability. The results suggest that banks exist the persistence of profitability and banks with higher capitalization, income diversification, net loans to total assets, liquid assets to deposit and short-term funding and lower cost to income ratio have higher ROAA and ROAE; but higher income diversification and liquid assets to deposit and short-term funding can reduce NIM. We find that capital not only plays as a buffer to absorb losses but also ameliorate profitability. Besides, Capital has positive effects on profitability both in commercial banks and non-commercial banks. However, the impact of capital on profitability is higher in non-commercial banks. We also conclude that commercial banks significantly influence the whole results since bank-specific and macro-economic variables have more significant effects on the profitability of commercial banks. Our paper contributes to bank managers and policymakers to improve the holding of capitalization level in the banks. Besides, bank managers should make a balance between lending expansion and maintaining liquidity and follow different profitability measures to make financial decisions.